The effect of the partnership between DanceSport couples on competitive performance: the mediating role of athlete engagement - Liu, Xiuxia; Wu, Bo; Weng, Xinghe; Shan, Qi (Frontiers in Psychology, 2023)
Objectives Although the positive association of partnership between DanceSport couples with competitive performance (CP) is documented, less is known about the mediating factors of this relationship. According to the related literature and self-determination theory (SDT), the present study finds and verifies that athlete engagement (AE) mediates the association between partnership and competitive performance. Methods A total of 242 Chinese sports dancers were recruited using the purposive sampling method. The Partnership Scale-DanceSport Couples (PS-DSC), the Athlete Engagement Questionnaire (AEQ), and the Competitive Performance Questionnaire (CPQ) were adopted to collect data. Results The obligatory instrumental ties, expressive ties, and interpersonal perception scores are all positively correlated with both athlete engagement and competitive performance, and athlete engagement scores are positively correlated with competitive performance. Athlete engagement completely mediates the association between obligatory instrumental ties and competitive performance, and it partially mediates the association between expressive ties, interpersonal perception, and competitive performance, with the mediating effect accounting for 25.29 and 24.40% of the total effect, respectively. Conclusion Athlete engagement mediates the association between DanceSport couples’ partnership and competitive performance. High levels of athlete engagement are needed to improve the chance of promoting obligatory instrumental ties, expressive ties, and interpersonal perception between DanceSport couples toward excellent competitive performance. Overall, the results represent an attempt to extend our understanding of the mechanisms by which the three partnership stereotype factors individually influence dancers’ cognitive and psychological states.